2011
DOI: 10.4069/kjwhn.2011.17.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fatigue and Postpartum Depression on Maternal Perceived Quality of Life (MAPP-QOL) in Early Postpartum Mothers

Abstract: Purpose: This study was done to identify effects of fatigue and postpartum depression on quality of life in early postpartum mothers. Methods: The data were collected from 130 mothers at four general hospitals in J and M metropolitan cities. Instruments used to collect the data for the study were the Fatigue Scale developed by Pugh (1993); Postpartum Depression Scale developed by Cox, Holden & Sagovsky (1987), and the Quality of Life Scale developed by Hill, Aldag, Hekel, Riner, G., & Bloomfield (2006). Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…We also found postpartum depression to be a major factor influencing women’s QoL. Previous studies have reported that postpartum depression reduces QoL in terms of physical and mental health [ 7 , 12 , 14 , 36 ]. Postpartum depression also tends to be exacerbated by postpartum fatigue or the burden of care for newborns in the early postpartum period, and it is highly likely to progress from mild depression to severe depression [ 30 ].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We also found postpartum depression to be a major factor influencing women’s QoL. Previous studies have reported that postpartum depression reduces QoL in terms of physical and mental health [ 7 , 12 , 14 , 36 ]. Postpartum depression also tends to be exacerbated by postpartum fatigue or the burden of care for newborns in the early postpartum period, and it is highly likely to progress from mild depression to severe depression [ 30 ].…”
Section: Discussionsupporting
confidence: 70%
“…QoL was measured using MAPP-QOL [ 2 ], for which the Korean version has well-established reliability and validity [ 14 ]. The MAPP-QOL has 40 items and two parts (satisfaction and importance), and the scores are calculated by weighting each satisfaction response with its paired importance response.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings of this study showed a negative correlation between mean scores of fatigue and PPD with QOL (r = -0.44, P < 0.01, r = -0.42), respectively. Moreover, a positive correlation was observed between fatigue and PPD (r = 0.59, P < 0.001) ( 31 ). In a study by Yeo et al on 211 women during first to third weeks postpartum PPD and QOL were assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The Ferrans and Powers QOL Index has 4 major domains: health and physical, social and economic, psychological and spiritual, and family [14]. Also, As mentioned previously, all studies [44][45][46][47] focused on populations with chronic diseases; however, 70% of the mothers in our sample did not have any chronic diseases, and 78% had at least one person to provide support for them. All these factors could explain the lack of correlation between PPF and QOL.…”
Section: Discussionmentioning
confidence: 84%